Irrigation Versus Suction Alone in Laparoscopic Appendectomy: Is Dilution the Solution to Pollution? A Systematic Review and Meta-Analysis. (April 2018) - Hajibandeh, Shahab; Hajibandeh, Shahin; Kelly, Adam; Shah, Jigar; Khan, Rao Muhammad Asaf; Panda, Nilanjan; Mansour, Moustafa; Malik, Sohail; Dalmia, Sanjay
Objectives . To investigate outcomes of peritoneal irrigation versus suction without irrigation in patients undergoing emergency laparoscopic appendectomy. Methods . We performed a systematic review and conducted a search of electronic information sources to identify all randomized controlled trials (RCTs) and observational studies investigating outcomes of irrigation versus suction alone in patients undergoing emergency laparoscopic appendectomy. We used the Cochrane risk of bias tool and the Newcastle-Ottawa scale to assess the risk of bias of RCTs and observational studies, respectively. Random-effects models were applied to calculate pooled outcome data. Results . We identified 3 RCTs and 2 retrospective observational studies, enrolling 2511 patients. Our results suggested that there was no difference between peritoneal irrigation and suction alone in terms of intraabdominal abscess rate (odds ratio = 2.39, 95% confidence interval [CI] = 0.49-11.74, P = .28), wound infection (risk difference = 0.00, 95% CI = −0.04 to 0.05, P = .85), and length of stay (mean difference = −1.02, 95% CI = −3.10 to 1.07, P = .34); however, peritoneal irrigation was associated with longer operative time (mean difference = 7.12, 95% CI = 4.33 to 9.92, P < .00001). Our results remained consistent when randomized trials, adult patients, and pediatric patients were analyzed separately. Conclusions. The best available evidence suggests that the peritoneal irrigation with normal saline during laparoscopic appendectomy does not provide additional benefits compared with suction alone in terms of intraabdominal abscess, wound infection, and length of stay but it may prolong the operative time. The quality of the best available evidence is moderate; therefore, high-quality RCTs, which are adequately powered, are required to provide more robust basis for definite conclusions.